2010
DOI: 10.1063/1.3502116
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear motion in carbonyl sulfide induced by resonant core electron excitation

Abstract: The angular anisotropy for selected dissociation channels is measured at resonantly excited states of ⌺ and ⌸ symmetries at the C and O K-shell ionization edges of carbonyl sulfide. While the kinetic energy released in the reaction is mainly independent of the excitation energy, the angular anisotropy and momentum correlation clearly show deformation of the OCS molecule in the C 1s −1 ‫1ء‬ state. The discovery of a two-body fragmentation channel SO + / C + with a well defined angular anisotropy indicates the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 26 publications
(32 reference statements)
4
23
0
Order By: Relevance
“…There have been a number of previous studies of the fragmentation dynamics in OCS following strong-field multiple ionization [42,[89][90][91][92][93], as well as similar studies using single photon, [8,90,[94][95][96][97][98], ion [99,100] and electron impact [101]. Many of these studies examined three-body breakup and did not focus on the bond rearrangement channel leading to SO + formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of previous studies of the fragmentation dynamics in OCS following strong-field multiple ionization [42,[89][90][91][92][93], as well as similar studies using single photon, [8,90,[94][95][96][97][98], ion [99,100] and electron impact [101]. Many of these studies examined three-body breakup and did not focus on the bond rearrangement channel leading to SO + formation.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the increasing attention devoted to these processes, so far most studies have focused on a single molecular species and have occurred under an assortment of experimental conditions. For example, the initiating ioniza-tion mechanism in previous bond rearrangement studies has variously included single [8,11,[37][38][39][40][41][42] and multiple photons [5,22,26,27,43] as well as electron [23,28,44] and heavy ion impact [2,7,30]. To assist in understanding these dynamics we examine bond rearrangement following ultrafast strong-field double ionization of three triatomic molecules: carbon dioxide, carbonyl sulfide and water.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study of carbonyl sulphide found a similar phenomenon leading to C + /OS + with a less pronounced anisotropy parameter interpreted as a signature of a significantly longer time scale for this transient isomerization. 36 The rearrangement in CO 2 can be seen as an intermediate case. Despite the larger inertia of oxygen, our analysis arrives at the same value of the anisotropy parameter as for acetylene.…”
Section: A Transient Isomerizationmentioning
confidence: 99%
“…6,26,27 Subsets of the data are then extracted by filtering by criteria for angle, momentum or fragmentation channel. 6,26,27 Subsets of the data are then extracted by filtering by criteria for angle, momentum or fragmentation channel.…”
Section: Experimental Methodsmentioning
confidence: 99%